Single-longitudinal-mode fiber laser with an ultra-narrow linewidth and extremely high stability obtained by utilizing a triple-ring passive subring resonator. (October 2020) - Wang, Zhengkang; Shang, Jianming; Mu, Kuanlin; Qiao, Yaojun; Yu, Song
Highlights: A stable TR-PSR-based SLM EDFL is proposed and experimentally demonstrated. The TR-PSR produced the high-quality mode filter effect to ensure the SLM output. The variation of the lasing wavelength of the EDFL is less than 0.008 nm. The linewidth of the proposed EDFL is as narrow as 690 Hz. Abstract: A single-longitudinal-mode (SLM) erbium-doped fiber laser (EDFL) with extremely high stability, an ultra-narrow linewidth and a high optical signal-to-noise ratio (OSNR) based on a triple-ring passive subring resonator (TR-PSR) is presented. The designed TR-PSR serves as a high-quality mode filter to suppress multi-longitudinal-mode (MLM) oscillation and guarantee SLM operation. The measured output power and the wavelength variations of the proposed EDFL over an observation period of 40 min are less than 0.01 dB and 0.008 nm, respectively. In addition, an ultra-narrow linewidth of 690 Hz and a high OSNR of 64 dB are obtained.